2003
DOI: 10.1080/10412905.2003.9712144
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Bactericidal Action of Oregano and Clove Essential Oils and of their Phenolic Major Components onEscherichia coliandBacillus subtilis

Abstract: The mechanism of the antimicrobial action of oregano (Ot-iganum compacturn) and clove essential oils was studied simultaneously with two phenolic components, namely thymol and eugenol. Escherichia coli and Bacillus subtilis were used as Gram negative and Gram positive bacterial models, respectively. The oils as well as their major components were capable of inducing cell lysis. Bacteria lysis was shown by the release of substances absorbing at 260 nm. For E. coZi, the results were similar to those obtained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
110
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 15 publications
10
110
0
10
Order By: Relevance
“…AgNPs have the ability to attach and destruct bacterial cell walls in a dosedependent manner (Cerny and Teuber, 1971;Rhayour et al, 2003;Ahmad et al, 2017) this is confirmed by Electron spin resonance spectroscopy studies which demonstrated that when AgNPs attached to the bacterial cell walls, the free radicals of the AgNPs were then released (Danilcauk et al, 2006;Kim et al, 2007;Swarnavalli et al, 2017).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…AgNPs have the ability to attach and destruct bacterial cell walls in a dosedependent manner (Cerny and Teuber, 1971;Rhayour et al, 2003;Ahmad et al, 2017) this is confirmed by Electron spin resonance spectroscopy studies which demonstrated that when AgNPs attached to the bacterial cell walls, the free radicals of the AgNPs were then released (Danilcauk et al, 2006;Kim et al, 2007;Swarnavalli et al, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…These released free radical seems to be the main causative agent responsible for final bacterial destruction and death (Devi et al, 2017); as these free radicals begin to make pores in the bacterial cell walls and membranes causing severe permeability of the bacterial cell membrane (Danilcauk et al, 2006;Kim et al, 2007;Swarnavalli et al, 2017), this is followed by releasing of periplasmic proteins and nucleic acids via cytoplasmic membrane, and so the bacterial cell death will be the final result (Cerny and Teuber, 1971;Rhayour et al, 2003;Ahmad et al, 2017;Swarnavalli et al, 2017). On the other hand, when AgNPs enter the bacterial cell, they form a low molecular weight region which begin to attack the respiratory chain, so consequently, the cellular signaling pathways will be changed by dephosphorylating assumed key peptide substrates on tyrosine residues (Sondi and Salopek-Sondi, 2004;Mulley et al, 2014;Su et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Present investigation revealed the inhibitory effect of clove extract on meat spoilage organisms, the effect being more profound because of the low surface pH of mutton caused by acidulant treatment (Sara Burt 2004). Essential oils are capable of inducing bacterial cell lysis, damaging both cell wall and membrane (Rhayour et al 2003). The hydrophobicity of essential oils enables them to partition in the lipids of the cell membrane and mitochondria, rendering them permeable and leading to leakage of cell contents causing cell death (Sara Burt 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Os picos dos cromatogramas estão identificados na Figura 2, onde é possível observar que o timol foi o segundo principal componente, depois do carvacrol. O timol esteve presente em três dos cinco OEO analisados (marcas A, B e C) com teores de 14,79% na marca A, 23,85% na marca B e 1,88% na marca C. inibitória contra bactérias Gram positivas e Gram negativas, inclusive SE (LIS-BALCHIN et al, 1998;DELAQUIS et al, 2002;SAGDIÇ;ÖZCAN, 2003, NAZER et al, 2005SARIKUS, 2006). Os óleos essenciais de condimentos podem ter muitos componentes, sendo os compostos fenólicos os principais responsáveis pelas propriedades antimicrobianas.…”
Section: Resultsunclassified